Gene expression profile unveils diverse biological effect of serum vitamin D in Hodgkin's and diffuse large B‐cell lymphoma. Issue 2 (13th December 2020) - Donati, Benedetta; Ferrari, Angela; Ruffini, Alessia; Manzotti, Gloria; Fragliasso, Valentina; Merli, Francesco; Zanelli, Magda; Valli, Riccardo; Luminari, Stefano; Ciarrocchi, Alessia
Abstract: The primary function of 25(OH)Vitamin D (VitD) is to control calcium; however, recent evidence associated serum VitD deficiency to high aggressiveness and worse outcome in different type of malignancies including lymphomas, and the reasons of such effect are to be defined. In this study, we investigated the association of VitD blood levels with gene expression in a retrospective cohort of 181 lymphomas (104 diffuse large B‐cell lymphomas [DLBCLs] and 77 classical Hodgkin's lymphomas [cHLs]) of whom 116 with available gene expression profiles (52 DLBCLs and 64 cHLs, respectively). In DLBCL, VitD deficiency did not cause significant alteration in gene expression suggesting different mechanisms of action including a possible systemic effect or an effect on pharmacokinetics. By contrast, in cHLs, VitD deficiency induced profound changes in the transcriptional program leading to the NF‐ κ B‐mediated activation of stress‐protective and pro‐survival pathways. Coherently, VitD signaling defined by vitamin D Receptor (VDR) expression analysis, resulted highly activated in cHLs but not in DLBCLs. Even if preliminary, these data represent the first evidence of a direct role of VitD in the biology of cHL and suggest a multimodality and disease‐specific activity of this vitamin in lymphomas.